2023
DOI: 10.1093/inthealth/ihad061
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and use of chorhexidine gel in umbilical cord care among postpartum women at Poly General Hospital, Enugu, Southeast Nigeria: a cross-sectional study

Chidinma E Israel,
Kareen O Attama,
Hope Chizolum Opara
et al.

Abstract: Background Sepsis in the first week or two of life is a major cause of newborn deaths. People from diverse cultural backgrounds use different substances for umbilical cord care. Evidence-based umbilical cord care practices have a large potential to lower infant morbidity and mortality linked to infection. This study investigated the knowledge and use of chlorhexidine gel for umbilical cord care. Methods A cross-sectional desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(33 reference statements)
0
0
0
Order By: Relevance
“…This finding is however higher than the rather low values of 11.7% and 2.8% reported in other studies. [25,26] Israel et al [27] and Aitafo et al [28] 28 reported chlorhexidine gel awareness of 60.7% and 63.3% but good knowledge scores of 47.1% and 34.2% respectively following further evaluation. These results differed from the high chlorhexidine cord care awareness 80.2% reported by Owusu et al 23] Awareness of the use of methylated spirit in this study by most of the respondents is in line with findings made by many other studies [19,21,[23][24][25][26]29].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is however higher than the rather low values of 11.7% and 2.8% reported in other studies. [25,26] Israel et al [27] and Aitafo et al [28] 28 reported chlorhexidine gel awareness of 60.7% and 63.3% but good knowledge scores of 47.1% and 34.2% respectively following further evaluation. These results differed from the high chlorhexidine cord care awareness 80.2% reported by Owusu et al 23] Awareness of the use of methylated spirit in this study by most of the respondents is in line with findings made by many other studies [19,21,[23][24][25][26]29].…”
Section: Discussionmentioning
confidence: 99%